Implementation Johari Window Technique With Intervention Individual Counseling (Client Centered Counseling) For Growth Of Self-Acceptance In Vocational High School X In Gresik - Jihan Sabila Ishmah; Nadhirotul Laily; Awang Setiawan Wicaksono (Psycho Holistic, 2022)
The problem with this study is the self-acceptance in Vocational High School. The purpose of this study is to know the use of assessment johari window techniques and individual counseling interventions with the centered person approach to cope low self-acceptance. This type of research is an experiment for one group design pre-test and post-test, data analysis techniques using comparison tests. The subject of this study are the class x students "x" that have low self-Acceptance scores. The results show that there is an increase in student acceptance after given the johari window technique and individual counseling intervention with the person centered to resolve self-acceptance. This is proven by a change in the score of 11 subject after given the johari window technique and individual counseling intervention from low category to medium and high category. It is also proven by an analysis of the comparative value of asymp sig. (2-tailed).003 or smaller than.005% alpha level (.05) which means there is a difference before and after intervention. It can be concluded that the assessment johari window technique and the individual counseling approach with effectively used in coping with the low self-acceptance of SMK students.